Implementasi Algoritma Dijkstra dalam Pencarian Klinik Hewan Terdekat - Shandy Yosua; Canro Sigalingging; Jamal Jipesya; Yuwan Jumaryadi (Jurnal Ilmiah FIFO, 2021)
The application of technology that is increasingly developing is almost felt to benefit in various aspects of life, one of which is in terms of searching for veterinary clinics. This study aims to help animal owners who have difficulty in finding clinics and shops that sell various kinds of animal needs closest to the user's location. This research uses the Scrum method, which consists of Product Backlog, Sprint Backlog, Sprint and Imcrement. The output from Dijkstra's algorithm can display the location and route of the closest veterinary clinic to application users wherever they are in an average of 4 minutes 29 seconds.